Mycelial growth of Pleurotus ostreatus in substrates supplemented with malt bagasse - da Silva, Larissa Fratini; Alves da Silva, Giovana Cristina Pinto [UNESP]; Martins, Olívia Gomes [UNESP]; de Souza Passos, José Raimundo [UNESP]; de Andrade, Meire Cristina Nogueira [UNESP] (Centro Universitario de Maringa, 2021)
Different supplementations based on agroindustrial residues, such as bark, bran, bagasse and others for the in vitro cultivation of the edible mushroom Pleurotus ostreatus. However, specialized literature lacks studies on the use of malt bagasse as supplementation in the culture medium for the cultivation of the mushroom. Large amounts of residues are generated by the brewing industry, and their use may be an effective way of supplementing substrate for the cultivation of edible fungi. Current study evaluated the mycelial growth of P. ostreatus in culture media supplemented with malt bagasse at different rates (0, 5, 10, and 20% on a dry basis). Evaluation criteria were radial growth and chemical characterization of the substrate. No significant interaction occurred between strains and substrates. When the two strains are compared, SB obtained higher mycelial growth than LC (65.35 mm and 63.46 mm, respectively). In the case of substrates, the highest growth was obtained in substrate S2, at an average of 67.75 mm. Other substrates did not differ statistically from each other (S1= 62.95 mm, S3= 64.06 mm and S4 = 62.85 mm). Results show that P. ostreatus developed on all substrates when supplemented with malt bagasse. On the other hand, the needs of each lineage should be taken into account with regard to rates used in the substrates for cultivation.
Crescimento micelial de Pleurotus ostreatus em substratos suplementados com bagaço de malte
Keywords: Beer-making; Edible mushrooms; Reuse Residues